Bretton Hall Hotel, Trinidad,W.I. - (:unkn) unknown (Hannau-Robinson Color Production, 2010)
Description printed on the back of the postcard: "[Bretton Hall] A home away from home...close to all activities, select the accommodation you prefer...room with balcony overlooking a sparkling pool...completely equipped furnished suite for long staying guests…airconditioned if you wish. Weekly - monthly rates available."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hotels--Trinidad and Tobago